Holarctic Species in the Pluteus podospileus Clade: Description of Six New Species and Reassessment of Old Names - Ševčíková, Hana; Malysheva, Ekaterina F; Antonín, Vladimír; Borovička, Jan; Dovana, Francesco; Ferisin, Giuliano; Eyssartier, Guillaume; Grootmyers, Django; Heilmann-Clausen, Jacob; Kalichman, Jacob; Kaygusuz, Oğuzhan; Lebeuf, Renée; et al. (Journal of fungi (Basel, Switzerland), 2023)
We studied the taxonomy of Pluteus podospileus and similar species using morphological and molecular (nrITS, TEF1-α) data, including a detailed study of the type collections of P. inflatus var. alneus, Pluteus minutissimus f. major, and P. granulatus var. tenellus. Within the P. podospileus complex, we phylogenetically confirmed six species in Europe, five in Asia, and eight in North America. Based on our results, we recognize P. seticeps as a separate species occurring in North America, while P. podospileus is limited to Eurasia. We describe six new species and a new variety: P. absconditus, P. fuscodiscus, P. gausapatus, P. inexpectatus, P. millsii, and P. notabilis and its variety, P. notabilis var. insignis. We elevate Pluteus seticeps var. cystidiosus to species rank as Pluteus cystidiosus. Based on the holotype of P. inflatus var. alneus, collections of P. inflatus identified by Velenovský, and several modern collections, we resurrect the name P. inflatus. Based on molecular analyses of syntypes of Pluteus minutissimus f. major and a holotype of Pluteus granulatus var. tenellus, we synonymize them under P. inflatus. We also increase our knowledge about the morphology and distribution of P. cutefractus.
Keywords: agaricales; new species; pluteaceae; type study; Celluloderma; holarctic